Faust und Geist Literatur und Boxen zwischen den Weltkriegen - Paterno, Wolfgang (2017)
Faust und Geist shall set out to find answers to the following questions: what are the motifs and continuing themes for the close link between fist fighting and writing? Which means are employed, what is the intent and what are the linguistic and formal techniques with which the fist fighting combat sport is translate into literature.